Dampak Kebisingan Kereta Api Terhadap Kenaikan Denyut Nadi Dan Gangguan Komunikasi Pada Masyarakat Di Kelurahan Sukosari Kecamatan Kartoharjo Madiun - Sunaryo Sunaryo (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2021)
ABSTRACT One type of land transportation that is in great demand by the public is trains. Railways, apart from having a positive impact, can also cause negative impacts, namely air pollution due to noise. The purpose of this study was to determine the effect of train noise on the increase in pulse rate and communication disturbances in communities around the railroad tracks. This research is an analytic survey with a cross sectional approach. The research population is people who live in areas along the railroad tracks in Sukosari Village, Kartoharjo Madiun District. The sample size is 30 people, the sampling technique uses purposive sampling. The research instrument was a sound level meter and a questionnaire. Statistical analysis with t-test, the set error rate was α, 0.05. The results of the research on noise measurement at a predetermined distance of 3 meters and 8 meters still exceed the noise threshold in residential areas, namely 55 dB. From the results of noise measurements for the north of the road is 67 dB and for the south of the road is 60 - 61 dB. Noise to society can affect 53.33% increase in pulse rate and 56.6% affect communication disturbances. The results of the analysis show that ρ (0.000)